Design A Wheeled Robot Prototype For Package Delivery - Muhammad Agiv Izzatur Firasyan; Faris Aqil Muhammad; Naofal Martfa (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Autonomous delivery robots offer innovative solutions to modern logistics challenges. This research explores the integration of the latest technologies into delivery robots, including a machine learning based hand gesture recognition feature. The hand gesture recognition feature is used for robotic container security, ensuring that only the sender and recipient can open and access the contents of the container. This technology uses machine learning algorithms to accurately detect and interpret the user's hand gestures. This advanced security system provides an extra layer of protection against theft and unauthorised access. In addition, these delivery robots are designed to improve operational efficiency and reduce environmental impact, meeting society's need for fast and accurate delivery services. While offering many benefits, the implementation of this technology faces challenges in terms of community acceptance and operational safety. This study provides insights into how delivery robot technology can be effectively integrated into the global logistics system, shaping the future of more efficient, connected and secure delivery services